Pengembangan E-Learning Menggunakan Schoology Berbasis Guided Discovery Learning pada Materi Laju Reaksi Kelas XI SMA atau MA - Hanan Habibah; Suryelita Suryelita (Universitas Negeri Padang, 2022)
The Covid-19 pandemic has an impact on the education sector, so technology is needed that can support the learning process, one of which is the use of e-learning. This research aims to develop and determine the validity of e-learning using Schoology based on Guided Discovery Learning (GDL) on the reaction rate material for class XI SMA or MA. The type of research used is development research using the plomp development model. The stages in the plomp model are limited to expert review and one to one evaluation, namely the prototype III. The expert review was carried out by six material expert validators and three media expert validators, while the one to one evaluation was carried out by three students with different abilities. The results of the assessment on each validity questionnaire were processed using the Aikens V formula. Based on the research results, e-learning using Schoology based on GDL model on the reaction rate material can be considered as valid. Further research is needed to determine the practicality and effectiveness of e-learning using Schoology based on GDL model.